1993
DOI: 10.1254/jjp.63.495
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of KF18259, a Novel 5-HT3-Receptor Antagonist, in Rats: Inhibition of the Distal Colonic Function

Abstract: ABSTRACT-We investigated the effects of KF18259 (endo-(8-methyl-8-aza-bicyclo[3.2.1]oct-3-yl)-1 isobutyl-2-oxo-1,2-dihydro-4-quinolinecarboxylate hydrochloride), a novel 5-HT3-receptor antagonist, in a variety of rat models, which are assumed to be mediated via 5-HT3 receptors, in comparison with those of5,6,7-tetrahydro-1H-benzimidazole hydrochloride), granisetron and ondansetron. KF18259 inhibited wrap-restraint stress-induced defecation. The doses of KF 18259 to inhibit wrap-restraint stress-induced defecat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…Moreover, cisplatin-induced free radical generation in the intestine (Sangeetha et al 1990) may lead to subsequent release of 5HT (Matsuki et al 1993;Cui et al 2016) which may act on peripheral 5HT3 to relax the stomach and lead to the delay in gastric emptying. Similar to the findings of earlier researchers (Kishibayashi et al 1993;Sharma & Gupta 1998;Ando & Takagi 2011;Yanai et al 2013), we also observed the reversal of the inhibition by ondansetron.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, cisplatin-induced free radical generation in the intestine (Sangeetha et al 1990) may lead to subsequent release of 5HT (Matsuki et al 1993;Cui et al 2016) which may act on peripheral 5HT3 to relax the stomach and lead to the delay in gastric emptying. Similar to the findings of earlier researchers (Kishibayashi et al 1993;Sharma & Gupta 1998;Ando & Takagi 2011;Yanai et al 2013), we also observed the reversal of the inhibition by ondansetron.…”
Section: Resultssupporting
confidence: 92%
“…Delayed gastric emptying most commonly gives rise to abdominal discomfort after meals, causing nausea and vomiting. These cisplatin-induced side effects in the gastrointestinal tract may be treated by metoclopramide (Roos et al 1981;Ullah et al 2015), 5HT3 receptor antagonists (Kishibayashi et al 1993;Yanai et al 2013) and antioxidants (Sharma & Gupta 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Colonic propulsion was assessed by the colonic transit of a charcoal marker, according to previous reports 21 . 22 Charcoal marker (a suspension of 5% charcoal and 10% Arabic gum in saline; 0.2 mL) was infused through the indwelling cannula followed by a 0.2‐mL saline flush.…”
Section: Methodsmentioning
confidence: 99%
“…The present study was designed to evaluate the action of α 2 ‐adrenoceptor antagonists on colonic propulsion in rats exposed to a stressful stimulus as well as nonstressed rats. We also compared the effects of α 2 ‐adrenoceptor antagonists on colonic motor function with the effects of clonidine, atropine and the 5‐hydroxytryptamine3 (5‐HT3) receptor antagonists ondansetron and YM060, which inhibit stress‐induced increase of colonic transit or faecal pellet output 19 –21 …”
Section: Introductionmentioning
confidence: 99%
“…The clinical study of Bearcroft et al (7) showed that the postprandial plasma concentration of 5-HT in IBS patients was higher than that in healthy volunteers. Furthermore, 5-HT 3 -receptor antago-nists have been reported to inhibit stress-induced abnormal defecation in animals (8,9), suggesting the involvement of 5-HT 3 receptors in the pathogenesis of IBS.…”
Section: Introductionmentioning
confidence: 99%